Mushroom hunting and consumption in twenty-first century post-industrial Sweden - Ingvar Svanberg; Hanna Lindh (BMC, 2019)
Abstract Background The pre-industrial diet of the Swedish peasantry did not include mushrooms. In the 1830s, some academic mycologists started information campaigns to teach people about edible mushrooms. This propaganda met with sturdy resistance from rural people. Even at the beginning of the last century, mushrooms were still only being occasionally eaten, and mostly by the gentry. During the twentieth century, the Swedish urban middle class accepted mushrooms as food and were closely followed by the working-class people. A few individuals became connoisseurs, but most people limited themselves to one or two taxa. The chanterelle, Cantharellus cibarius Fr., was (and still is) the most popular species. It was easy to recognize, and if it was a good mushroom season and the mushroomer was industrious, considerable amounts could be harvested and preserved or, from the late 1950s, put in the freezer. The aim of this study is to review the historical background of the changes in attitude towards edible mushrooms and to record today's thriving interest in mushrooming in Sweden. Methods A questionnaire was sent in October and November 2017 to record contemporary interest in and consumption of mushrooms in Sweden. In total, 100 questionnaires were returned. The qualitative analysis includes data extracted from participant and non-participant observations, including observations on activities related to mushroom foraging posted on social media platforms, revealed through open-ended interviews and in written sources. With the help of historical sources, including earlier studies and ethnographical data collections, a diachronic analysis is given to describe the changes over time. Results and discussion During the last 100 to 140 years, Sweden has changed from a mycophobic to a mycophilic society with a passionate interest in the utilization of wild mushrooms. In the late twentieth century, various social institutions connected with mushroom hunting evolved. Evening classes, study circles, clubs, exhibitions, consultants, and a wide array of handbooks promoted this interest. In the early twenty-first century, mushrooming has become widely accepted, especially among the middle class, but also among Swedes in general. The so-called hipster-generation, born in the 1990s, harvests mushrooms due to their interest in producing their own food. This group often uses social media to identify edible species. Most people who go mushrooming gather only a few species. There are, however, some dedicated individuals who have become hobby specialists and who know a wide diversity of taxa. A few study participants reported that they were afraid of not being able to distinguish between poisonous fungi species and edible ones and therefore refrain from picking any wild mushrooms at all. However, they still consume cultivated mushrooms, such as Agaricus bisporus (J.E. Lange) Imbach, bought in grocery stores or served in cafes and restaurants. Conclusion Swedish society has changed rapidly during the last decades and so has the interest in mushrooming among its members. Throughout the second part of the twentieth century, the flow of information about mushrooms has continued through lecturers, courses, media, exhibitions, and even associations. Walking in forestland is also an important leisure activity for many urban Swedes, and in the early twenty-first century, mushrooming has also become a thriving pastime among people with an urban lifestyle.